Effect of EDTA treatment method on leaching of Pb and Cr by Phragmites australis (Cav.) Trin. Ex Steudel (common reed) - Ebrahimi, M. (Caspian Journal of Environmental Sciences, 2015)
One of the major problems about the chelant-enhanced phytoextraction is the potential metal leaching associated with chelant application. A glasshouse pot experiment was conducted to investigate phytoextraction efficiency of common reed (Phragmites australis (Cav.) Trin. ex Steudel) for Lead and Chromium and to determine EDTA (ethylenediaminetetraacetic acid) enhancement of the mobility and phytoextraction of Pb and Cr and the potential for leaching of metals during the phytoextraction process. The results revealed that the bioconcentration factors of underground organs of the plant species were relatively higher than the bioconcentration factors of shoots and metals concentrations in the plant organs decreased in the order of root› rhizome› leave› stem. Thus, P. australis would be applicable for Pb and Cr phytostabilization. Addition of EDTA (0, 2.5, 5, 10 mmol.kg−1) to polluted pots with Pb and Cr significantly enhanced the mobility of soil metals and led to elevated soil solution concentrations of Pb and Cr. Positive correlation coefficients were found between treatment time and heavy metals concentrations in the plant organs. Optimum phytoextraction was observed when 5mmol. kg−1 EDTA was added in single dosage, 60 days for Pb and double dosage for Cr, after the plant cultivation and, consequently, soil Pb and Cr concentration decreased with the passage of time. It can be concluded that P. australis can remediate Pb-Cr contaminated soils and EDTA had potential to promote the uptake of Pb and Cr for common reed, but with respect to its environmental leaching risk to ground waters, low dose should be used.